Global MicroRNAs Expression Profile Analysis Reveals Possible Regulatory Mechanisms of Brain Injury Induced by Toxoplasma gondii Infection - Hou, Zhaofeng; Wang, Lele; Su, Dingzeyang; Cai, Weimin; Zhu, Yu; Liu, Dandan; Huang, Siyang; Xu, Jinjun; Pan, Zhiming; Tao, Jianping (Frontiers in Neuroscience, 2022)
Toxoplasma gondii (T. gondii) is an obligate intracellular parasitic protozoan that can cause toxoplasmosis in humans and other endotherms. T. gondii can manipulate the host gene expression profile by interfering with miRNA expression, which is closely associated with the molecular mechanisms of T. gondii-induced brain injury. However, it is unclear how T. gondii manipulates the gene expression of central nervous system (CNS) cells through modulation of miRNA expression in vivo during acute and chronic infection. Therefore, high-throughput sequencing was used to investigate expression profiles of brain miRNAs at 10, 25, and 50 days post-infection (DPI) in pigs infected with the Chinese I genotype T. gondii strain in this study. Compared with the control group 87, 68, and 135 differentially expressed miRNAs (DEMs) were identified in the infected porcine brains at 10, 25, and 50 DPI, respectively. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis showed that a large number significantly enriched GO terms and KEGG pathways were found, and were mostly associated with stimulus or immune response, signal transduction, cell death or apoptosis, metabolic processes, immune system or diseases, and cancers. miRNA–gene network analysis revealed that the crucial connecting nodes, including DEMs and their target genes, might have key roles in the interactions between porcine brain and T. gondii. These results suggest that the regulatory strategies of T. gondii are involved in the modulation of a variety of host cell signaling pathways and cellular processes, containing unfolded protein response (UPR), oxidative stress (OS), autophagy, apoptosis, tumorigenesis, and inflammatory responses, by interfering with the global miRNA expression profile of CNS cells, allowing parasites to persist in the host CNS cells and contribute to pathological damage of porcine brain. To our knowledge, this is the first report on miRNA expression profile in porcine brains during acute and chronic T. gondii infection in vivo. Our results provide new insights into the mechanisms underlying T. gondii-induced brain injury during different infection stages and novel targets for developing therapeutic agents against T. gondii.